Figures of Time : Affect and the Television of Preemption - Pape, Toni, 1983- (Book collections on Project MUSE., 2019)
Toni Pape examines contemporary television that often presents a conflict-laden conclusion first before relaying the events that led up to that inevitable ending, showing how this narrative structure attunes audiences to the fear-based political doctrine of preemption--a logic that justifies preemptive action to nullify a perceived future threat.